2022
DOI: 10.3390/jmse10091193
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Solvents on the Extraction of Compounds from Different Parts of Undaria pinnatifida (Harvey) Suringar

Abstract: Asian kelp (Undaria pinnatifida) is a brown alga mainly grown and consumed in East Asian countries such as China, Japan, and Korea. To date, studies on the various biological activities of Asian kelp have been conducted; however, studies focusing on the different parts of Asian kelp and their use for other than food are limited. Therefore, in this study, different parts of Asian kelp, namely, whole U. pinnatifida (UP), U. pinnatifida blade (UPB), U. pinnatifida stipe (UPS), and U. pinnatifida sporophylls (UPSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…The blade extract showed the highest total polyphenol content. Similar total polyphenol contents have been reported for U. pinnatifida in previous studies [121,122]. Here, a good correlation between the results obtained using the Folin-Ciocalteu and TEAC assays was highlighted, and in particular, both tests indicated a higher antioxidant activity and phenol content of the blade extracts compared to the sporophyll and holdfast extracts.…”
Section: Discussionsupporting
confidence: 90%
“…The blade extract showed the highest total polyphenol content. Similar total polyphenol contents have been reported for U. pinnatifida in previous studies [121,122]. Here, a good correlation between the results obtained using the Folin-Ciocalteu and TEAC assays was highlighted, and in particular, both tests indicated a higher antioxidant activity and phenol content of the blade extracts compared to the sporophyll and holdfast extracts.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies by Huang et al [16] and Kim [17] showed that the physiologically active constituents of S. baicalensis wild-type root have low solubility in hot water and benzene extraction, but can be readily extracted using solvents, such as methanol, ethanol, and acetone; however, the selection of a suitable solvent based on the polarity of the compounds is an important task [18]. The yield and function of the dissolved bioactive compounds' composition might be affected depending on the extraction solvent employed.…”
Section: Introductionmentioning
confidence: 99%